Effectiveness of Online Learning Models in the Communication Sciences Program During the COVID-19 Pandemic - Fitria Widiyani Roosinda; Anita Agustina Wulandari; Edelweis Putri Prima (LPPM Stikosa - AWS, 2025)
This research is a descriptive quantitative study that focuses on the evaluation of online classes using online media. The research population consists of 50 active students in the 1st, 3rd, and 7th semesters, selected using the simple random sampling technique, and 5 lecturers from Communication Studies Program Bhayangkara University Surabaya. The data collection instrument used was an online lecture questionnaire. Data analysis uses descriptive statistics. The research results show that students assess online classes using online media as ineffective (39%), very ineffective (19%), effective (23%), and just okay (19%). In the results of this study, there were no (0%) respondents who rated online learning as very effective. Finally, to improve the quality of online lectures during the COVID-19 pandemic, the suggestions from communication studies lecturers and students are (1) providing more adequate quota subsidies for the continuity of online lectures (2) attention to the timing of online classes in accordance with the class schedule, (3) optimal and updated notifications or announcements, (4) upgrade the Bhayangkara University Surabaya SIM e-learning system, especially on the attendance and assignment upload features that still frequently encounter issues, (5) the selection of materials in the video must be based on criteria of easily understandable language, (6) implementation of more engaging activity models such as games and others, (7) during online classes, it is expected that everyone will be on camera (8) increasing server speed,(9) increasing student engagement during online classes and, (10) providing structured evaluations for assessment materials.